The Industrial Organization of Online Education - Cowen, Tyler; Tabarrok, Alex (American Economic Review, 2014)
Online education has flexibility and cost advantages over in-class teaching and these advantages will grow with improvements in information technology. We consider likely market structures given that the quality aspects of online education exhibit endogenous fixed costs. Concentration in the market for courses could be high, as it is currently in the market for textbooks. The not-for-profit sector will exhibit lower costs, lower concentration, and possibly zero price.